2016
DOI: 10.5658/wood.2016.44.6.852
|View full text |Cite
|
Sign up to set email alerts
|

Study on Rapid Measurement of Wood Powder Concentration of Wood-Plastic Composites using FT-NIR and FT-IR Spectroscopy Techniques

Abstract: Wood-plastic composite (WPC) is a promising and sustainable material, and refers to a combination of wood and plastic along with some binding (adhesive) materials. In comparison to pure wood material, WPCs are in general have advantages of being cost effective, high durability, moisture resistance, and microbial resistance. The properties of WPCs come directly from the concentration of different components in composite; such as wood flour concentration directly affect mechanical and physical properties of WPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A total of nine compounding combinations were designed, as shown in Table 1, by varying the ratios of wood chips and PE, but the proportions of other ingredients was maintained as 17%. It should be noted that determination of wood content in the WPC is crucial and can be examined using either thermogravimetric analysis and Fourier transform near-infrared and Fourier transform infrared spectroscopy (Cho et al, 2016). Experiments were carried out to determine the optimal mixture with the highest flexural strength value and the least water absorption or dimensional swelling value.…”
Section: Compounding Design For Wood Blockmentioning
confidence: 99%
“…A total of nine compounding combinations were designed, as shown in Table 1, by varying the ratios of wood chips and PE, but the proportions of other ingredients was maintained as 17%. It should be noted that determination of wood content in the WPC is crucial and can be examined using either thermogravimetric analysis and Fourier transform near-infrared and Fourier transform infrared spectroscopy (Cho et al, 2016). Experiments were carried out to determine the optimal mixture with the highest flexural strength value and the least water absorption or dimensional swelling value.…”
Section: Compounding Design For Wood Blockmentioning
confidence: 99%
“…A near-infrared (NIR) spectrum acquired from a surface of wood is a good example. The NIR region contains information about the chemical characteristics of the wood (Cho et al, 2016;Yang et al, 2017). Therefore, it has potential for the classification of wood species.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of NIR spectroscopy are its nondestructive testing and rapid measurement capabilities (Blanco, 2002;Pasquini, 2003;Porep et al, 2015). In wood science, NIR application has been widely studied to determine the wood's physical properties (Schimleck and Evans, 2003;Jiang et al, 2006;Yang et al, 2017), chemical aspects (Alves et al, 2006;Watanabe et al, 2006;Üner et al, 2011;Cho et al, 2016), mechanical strength (Thumm and Meder, 2001;Zhao et al, 2009;Hovarth et al, 2011), and moisture content (Thygesen and Lundqvist, 2000;Eom et al, 2010;Chang et al, 2015;Yang et al, 2015). In this context, some classification studies using NIR spectroscopy have recently been reported because chemical composition varies by species.…”
Section: Introductionmentioning
confidence: 99%